Ministry of Trade and Industry Decree No. 1081 of the year 2017 Concerning the Definition of Medium, Small and Micro Projects = وزارة التجارة والصناعة قرار رقم 1081 لسنة 2017 بشأن تعريف المشروعات المتوسطة والصغيرة ومتناهية الصغر - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic